What Drives Gig Worker Success? Investigating the Impact of Relevant Experience and Self-Directed Learning - Putra, Hamzah Muhammad Mardi; Martono, Besar Agung; Said, Jamaliah; Setyaningrum, Retno Purwani (Jurnal Manajemen Bisnis, 2025)
Research aims: This study aims to explore the relationship between self-directed learning, relevant work experience, and digital freelancers' performance in Southeast Asia, especially Indonesia and Malaysia, by considering the role of intrinsic motivation as a moderating variable.Design/Methodology/Approach: The study was conducted in two countries, Indonesia and Malaysia, involving 235 freelance respondents from various digital fields. Data were analyzed using SEM-PLS.Research findings: The results indicate that relevant experience is an important bridge between self-learning and work performance. Interestingly, intrinsic motivation does not act as a reinforcement of this relationship.Theoretical Contribution/Originality: The present study expands theoretical understanding of how work competencies are formed in the gig economy ecosystem, as well as how internal motivation needs to be viewed more contextually through self-determination theory (SDT) framework.Practitioners/Policy Implications: These findings reinforce the urgency of developing individual learning capacity and creating a support ecosystem, especially in a country like Indonesia that still lacks formal regulation and protection for freelancers, compared to Malaysia, which has been more progressive in recognizing and supporting the role of freelancers in the digital economy.Research Limitations/Implications: As the approach used is quantitative and cross-sectional, the data only shows conditions at a certain point in time. Future longitudinal studies are recommended to capture changes in behavior and performance in more depth over time.